Pengukuran Kinerja Keuangan dengan Pendekatan Value Based Management pada PT Indah Kiat Pulp & Paper Tbk Periode 2019–2024 - Rafidah Kalistyaningrum; Asep Muslihat; Hari Sulistiyo (Jurnal EMT KITA, 2026)
This study aims to analyze the financial performance of PT Indah Kiat Pulp & Paper Tbk for the 2019–2024 period using Value-Based Management techniques, namely Economic Value Added (EVA) and Market Value Added (MVA). This study employs a descriptive quantitative analysis approach using secondary data obtained from PT Indah Kiat Pulp & Paper’s annual financial reports published on the Indonesia Stock Exchange. The results show that EVA consistently remained negative throughout the study period, indicating that the company has not been able to create Economic Value Added because the operating profit generated was insufficient to cover the cost of capital incurred. On the other hand, MVA remained consistently positive because the company’s market value exceeded the invested capital, indicating that the company was able to create Market Value Added and gain investor confidence. PT Indah Kiat Pulp & Paper Tbk has proven capable of creating market value for its shareholders, as reflected by its positive MVA, although it has not yet succeeded in creating economic value-added based on the EVA approach. Therefore, the company needs to improve capital efficiency and profitability in order to generate sustainable economic value-added.